2011
DOI: 10.3109/09638288.2011.582922
|View full text |Cite
|
Sign up to set email alerts
|

Driving and driving cessation after traumatic brain injury: processes and key times of need

Abstract: The processes surrounding driving and driving cessation after TBI are complex. Informational, support and practical needs differ at the different times. There are key times where people may need further support to improve rehabilitation outcomes. Rehabilitation approaches may particularly need to provide clear, consistent information about driving restrictions, and the process required for returning to driving. While recovery time appears necessary for allowing a safe return to driving, active support for cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(57 citation statements)
references
References 25 publications
2
54
0
1
Order By: Relevance
“…There was one article that was specific to individuals with stroke (Griffen et al, 2009) and a study reported over two articles that was unique to individuals with TBI (Liddle et al, 2011;Liddle, Fleming, et al, 2012). In all the articles, there was an almost equal distribution of spouses and other family members (Griffen et al, 2009;Liddle et al, 2011;Liddle, Fleming, et al, 2012 Prior to stopping driving, 63% of females were taking household shopping trips compared to 34% of the males.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There was one article that was specific to individuals with stroke (Griffen et al, 2009) and a study reported over two articles that was unique to individuals with TBI (Liddle et al, 2011;Liddle, Fleming, et al, 2012). In all the articles, there was an almost equal distribution of spouses and other family members (Griffen et al, 2009;Liddle et al, 2011;Liddle, Fleming, et al, 2012 Prior to stopping driving, 63% of females were taking household shopping trips compared to 34% of the males.…”
Section: Resultsmentioning
confidence: 99%
“…There was one article that was specific to individuals with stroke (Griffen et al, 2009) and a study reported over two articles that was unique to individuals with TBI (Liddle et al, 2011;Liddle, Fleming, et al, 2012). In all the articles, there was an almost equal distribution of spouses and other family members (Griffen et al, 2009;Liddle et al, 2011;Liddle, Fleming, et al, 2012 Prior to stopping driving, 63% of females were taking household shopping trips compared to 34% of the males.  Individuals who were driven by family members for non-essential travel (e.g., leisure trips) rose from 17 to 76%  13% of caregivers reported giving up the worker role while 33% reported missing work occasionally  58% of family members rated the older driver's driving as "good" or "excellent" while 81% individuals did so (p=0.0342)  Regarding driving decisions, 42% of family members and 11% of older drivers felt that they should not be driving (p=0.0027)  While the older driver reported that advice to stop driving all came from their adult children, family members reported that the older driver's friends (22%), adult children (67%) and spouses (11%) had advised as well.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations